IbM Strategi Peningkatan Pendapatan Masyarakat Melalui Program Diversifikasi Produk dan Digital Marketing pada Anggota Aisyiyah Ranting Bojanegara Kecamatan Sigaluh Kabupaten Banjarnegara - Fatmah Bagis; Bima Cinintya Pratama; Mastur Mujib Ikhsani; Akhmad Darmawan (LPPM ITB AAS Indonesia Surakarta, 2020)
Changes in consumer tastes of food products, tend to take place quickly. Products that are currently excellent can be one or two months down. Various types of products are increasingly varied, one after another. No matter how bestselling a compilation product will meet the saturation point. Thorny palm fruit is widely produced in the village of Bojanegara, Sigaluh District, Banjarnegara Regency. So far, thorny palm farmers sell their crops directly to the market. Although there are one or two farmers who process thorny palm into thorny palm crackers. Previously, there were many preparations and other creations that could be produced from the thorny palm fruit. The purpose of this activity was to increase the income of the community members of Aisyiyah Branch Bojanegara, Sigaluh Subdistrict, Banjarnegara District, by diversifying products from thorny palm fruit and using digital marketing as marketing media. This activity was carried out for 1 day with a total of 38 participants. The method used in this activity is the lecture, question and answer, and discussion methods. The results of this activity add to the knowledge participants with their activeness and demand to be able to increase revenue through product diversification and the application of digital marketing as a media product promotion. Participants immediately practiced various kinds of preparations that could be produced from thorny palm fruit and applied social media as a means of promotion. Keywords: training, thorny palm, digital marketing, Aisyiyah Ranting Bojanegara